ANALISIS SEKTOR POTENSIAL DALAM MENINGKATKAN PEREKONOMIAN DI KABUPATEN HALMAHERA SELATAN BERDASARKAN PENDEKATAN DYNAMIC LOCATION QUOTIENT (DLQ) - Putri Nurul Hidayah; Rifki Khoirudin; Muhammad Safar Nasir (LP2M Universitas Bina Bangsa, 2023)
The development of a region that is increasingly advanced in the current era of regional autonomy, causing competition between regions to become tighter. In order for the regional economy to increase, people's welfare remains stable, the local government must increase competitiveness in the region. In order for regional development to be more focused, one of the efforts that can be done is to detect the leading sectors of the region. The area to be studied is North Maluku Province, South Halmahera Regency in 2016-2021, using data from the Central Statistics Agency (BPS). This study aims to determine the leading sectors in Halmahera Selata Regency so that local governments focus on developing their regions. The shift share (SS), location quotient (LQ), and Dynamic Location Quotient (DLQ) analysis approaches were used in analyzing the largest sector of South Halmahera Regency